Geothermal Energy from the Main Karoo Basin (South Africa): An Outcrop Analogue Study of Permian Sandstone Reservoir Formations. (November 2016) - Campbell, Stuart A.; Lenhardt, Nils; Dippenaar, Matthys A.; Götz, Annette E.
Abstract: The geothermal potential of the Main Karoo Basin has not been addressed in the past. A first assessment of Permian sandstone formations in the Eastern Cape Province, including down-hole temperature data from deep boreholes, and evaluation of groundwater temperature and heat flow values from literature leads to 3130 TWh (11.3 EJ) of power generation potential within the central and southern parts of the basin. The low permeability lithotypes may be operated as enhanced geothermal systems (EGS), depending on the fracture porosity in the deeper subsurface. In some areas auto-convective thermal water circulation might be expected and direct heat use becomes reasonable.